Investigation Into The Use of Surgacane Bagasse As A Fibre Reinforcement in Concrete - Wayne, Patrick Christian Areki (2017)
Agriculture waste is a growing concern in much of the worlds countries as the management of waste from agriculture industries are growing with their development. Researchers worldwide are exploring the means of using such waste as a means to tackle the environmental impacts they pose. This Projects explores the use for sugarcane bagasse fiber , a derivative of the sugar industry as a fiber reinforcing material in concrete. Three concrete Samples are being tested containing 3%, 6%, 8% of sugarcane bagasse fiber. Concrete strength was tested at 7, 14 and 28 days of curing and a comparative analysis with plain control concrete was made. In general, the Sugarcane bagasse concrete was unable to achieve the desired strength of 30.MP a due to the sugarcane fiber adversely affecting the setting time of concrete as well as inhibiting the proper binding of concrete constituents. However, after physical observations and in depth analysis of results, valid recommendations have been made to improve further studies.